Intramuscular administration of glyoxylate rescues swine from lethal cyanide poisoning and ameliorates the biochemical sequalae of cyanide intoxication. (3rd November 2022) - Bebarta, Vik S; Shi, Xu; Zheng, Shunning; Hendry-Hofer, Tara B; Severance, Carter C; Behymer, Matthew M; Boss, Gerry R; Mahon, Sari; Brenner, Matthew; Knipp, Gregory T; Davisson, Vincent Jo; Peterson, Randall T; et al.
Abstract: Cyanide—a fast-acting poison—is easy to obtain given its widespread use in manufacturing industries. It is a high-threat chemical agent that poses a risk of occupational exposure in addition to being a terrorist agent. FDA-approved cyanide antidotes must be given intravenously, which is not practical in a mass casualty setting due to the time and skill required to obtain intravenous access. Glyoxylate is an endogenous metabolite that binds cyanide and reverses cyanide-induced redox imbalances independent of chelation. Efficacy and biochemical mechanistic studies in an FDA-approved preclinical animal model have not been reported. Therefore, in a swine model of cyanide poisoning, we evaluated the efficacy of intramuscular glyoxylate on clinical, metabolic, and biochemical endpoints. Animals were instrumented for continuous hemodynamic monitoring and infused with potassium cyanide. Following cyanide-induced apnea, saline control or glyoxylate was administered intramuscularly. Throughout the study, serial blood samples were collected for pharmacokinetic, metabolite, and biochemical studies, in addition, vital signs, hemodynamic parameters, and laboratory values were measured. Survival in glyoxylate-treated animals was 83% compared with 12% in saline-treated control animals ( p  < .01). Glyoxylate treatment improved physiological parameters including pulse oximetry, arterial oxygenation, respiration, and pH. In addition, levels of citric acid cycle metabolites returned to baseline levels by the end of the study. Moreover, glyoxylate exerted distinct effects on redox balance as compared with a cyanide-chelating countermeasure. In our preclinical swine model of lethal cyanide poisoning, intramuscular administration of the endogenous metabolite glyoxylate improved survival and clinical outcomes, and ameliorated the biochemical effects of cyanide.